Master class of the use of competence-oriented and personoriented tasks on the subject of «Theory of intercultural communication» - Daulet, F N (Journal of Oriental Studies, 2016)
In this article the author presents the competence-oriented and person-oriented educational technology, which is actively used by the author in the pedagogical process. The main idea of the article is based on republican master class conducted by the author in the Faculty of Oriental Studies in October 2014.